Bahasa Indosenisa - safitri, yani okta; hikmah, Hikmah (SCIENTIA JOURNAL, 2023)
One of the keys to the success of an organization is intrinsically related to high-performing people in the organization. In accordance with this way, employees are guided to improve their performance. A quality workforce guarantees optimal work results in accordance with work goals, employees who work with the desire to fulfill their daily needs and other supporting needs. This research is aimed at PT Citra Tubindo Tbk Batam, the data collection method is through a questionnaire with a sample of 125 respondents. The analytical method used is multiple linear regression. From the test results, the t count of the motivational variable X1 is 3,824, which is greater than the t table (1,979) or the significance value of the motivational variable is 0,000, which is less than 0.05, so the hypothesis is accepted.Keywords: : employee performance: motivation, spirit at work